Good-bye to the Celtic Tiger? - Hazelkorn, Ellen (International Higher Education, 2010)
Higher education in Ireland faces challenges. In order to be competitive with the world-class universities, Irish higher education needs a strategic approach at the system level, an increase of investment, and a consideration of performance-based funding for greater productivity. The Irish government has implemented two initiatives regarding reform and investments in 2008. After the global economic crisis, though many countries took stimulus measures, Ireland conducted massive cuts in public expenditure.